Play, sing and dance : an introduction to Orff Schulwerk - Goodkin, Doug, ....- (London : Schott, 2013)
Teacher and performer Doug Goodkin presents an overview of the dynamic approach to music education known as Orff Schulwerk. In this comprehensive look at the many facets of this timeless practice, the author hopes to re-imagine its import in the lives of children, schools and culture at large in contemporary times. Carl Orff's educational ideas could not have an advocate more well equipped by fortune and disposition. Inspired initially by Avon Gillespie, who embodied playing, singing and dancing, Doug Goodkin also brings to his teaching a first-hand, intensive experience of the indigenous music and dance of many continents and peoples.